Mechanisms of Levetiracetam in the Control of Status Epilepticus and Epilepsy - Deshpande, Laxmikant S.; DeLorenzo, Robert J. (Frontiers in Neurology, 2014)
Status epilepticus (SE) is a major clinical emergency that is associated with high mortality and morbidity. SE causes significant neuronal injury and survivors are at a greater risk of developing acquired epilepsy and other neurological morbidities, including depression and cognitive deficits. Benzodiazepines and some anticonvulsant agents are drugs of choice for initial SE management. Despite their effectiveness, over 40% of SE cases are refractory to the initial treatment with two or more medications. Thus there is an unmet need of developing newer anti-SE drugs. Levetiracetam (LEV) is a widely prescribed anti-epileptic drug that has been reported to be used in SE cases, especially in benzodiazepine-resistant SE or where phenytoin cannot be used due to allergic side-effects. Levetiracetam’s non-classical antiepileptic mechanisms of action, favorable pharmacokinetic profile, general lack of central depressant effects and lower incidence of drug interactions contributes to its use in SE management. This review will focus on LEV’s unique mechanism of action that makes it a viable candidate for SE treatment.